Odpowiedzi

Najlepsza Odpowiedź!
2009-11-17T20:55:36+01:00
A.4/5+1/10
8/10+1/10=9/10

1/6+2/3
1/6+4/6=5/6

8/9+-1/3
8/9-3/9=5/9

1i3/10-1/5
1i3/10-2/10=1i1/10

2/3+1/5
10/15+3/15=13/15

4/7+1/2
8/14+4/12=1

2i2/5+3i1/2
2i4/10+3i5/10=5i9/10

4i1/2-2i3/5
4i5/10-2i6/10=1i1/10

4i1/4-2i2/3
4i3/12-2i8/12=1i5/12

5i1/9-1i5/6
5i2/18-1i15/19=3i3/19

2i1/15-1/10
2i2/30-3/30=1i1/30

5i5/13-3i1/2
5i10/26-3i13/26=1i3/26
2009-11-17T21:13:11+01:00
0.9
0.87
0.6
0.2
0.9
1.1
2.8
2.3
0.2
0.46
0.45
1.2
-0,05
-04
0,1
-1.2
2009-11-17T21:21:42+01:00
4/5+1/10= 8/10+1/10= 9/10

1/6+2/3= 1/6+4/6= 5/6

8/9+1/3= 8/9+3/9= 11/9= 1i2/9
w przypadku powyżej nie wiem czy przed 1/3 nie ma minusa, a jeśli jest to wynik poniżej, jeśli nie ma to wynik powyżej
8/9+-1/3= 8/9+-3/9= 5/9

1i3/10-1/5= 1i3/10-2/10= 1i1/10

2/3+1/5= 10/15+3/15= 13/15

4/7+1/2= 8/14+7/14= 15/14= 1i1/14

2i2/5+3i1/2= 2i4/10+3i5/10= 5i9/10

4i3/7+2i2/3= 4i9/21+2i14/21= 6i23/21= 7i2/21

4/5-2/3= 12/15-10/15= 2/15

5/7-1/4= 20/28-7/28= 13/28

2i3/8-1i1/6= 2i9/24-1i4/24= 1i5/24

4i1/2-2i3/5= 4i5/10-2i6/10= 3i15/10-2i6/10= 1i9/10

4i1/4-2i2/3= 4i3/12-2i8/12=3i15/12-2i8/12= 1i7/12

5i1/9-1i5/6= 5i2/18-1i15/18= 4i20-1i15/18= 3i5/18

2i1/15-1/10= 2i2/30-3/30= 1i32/30-3/30= 1i29/30

5i5/13-3i1/2= 5i10/26-3i13/26= 4i36/26-3i13/26=1i23/26